PENGARUH LINGKUNGAN KERJA DAN BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN PADA PT. GLOBAL MOBILITY SERVICE INDONESIA - Lukman Achmad; Fikriah Fikriah; Fitria Jayanti Attasa (JOEL: Journal of Educational and Language Research, 2022)
The purpose of this study was to determine: The influence of the work environment and corporate culture on employee performance at PT. Global Mobility Service Indonesia. The subjects of this study were 21 respondents. The sampling method used in this study is the saturated sample method. The method of data collection in this study is the survey method. The calculation method of validity and reliability analysis, normality test, linearity test, heteroscedasticity, correlation analysis, t test, ANOVA test, and coefficient of determination with SPSS version 25 analysis tool. positive and significant influence between work environment and corporate culture on employee performance with a value of f count = 6.588 which is greater than f table = 3.55. From the results of the t-test of the work environment, the value of t-count = 1.206 is smaller than t-table = 1.734, this shows that the work environment has no effect and is not significant on employee performance. For corporate culture, the value of t count = 1.206 is greater than t table = 2.101, this shows that corporate culture has a positive and significant influence on employee performance.